2014
DOI: 10.7150/thno.9423
|View full text |Cite
|
Sign up to set email alerts
|

Co-delivery of Doxorubicin and Bmi1 siRNA by Folate Receptor Targeted Liposomes Exhibits Enhanced Anti-Tumor Effects in vitro and in vivo

Abstract: Bmi1 gene overexpression is found in various human tumors and has been shown as a potential target for gene treatment. However, siRNA-based treatments targeting Bmi1 gene have been restricted to limited delivery, low bioavailability and hence relatively reduced efficacy. To overcome these barriers, we developed a folate receptor targeted co-delivery system folate-doxorubicin/Bmi1 siRNA liposome (FA-DOX/siRNA-L). The FA-DOX/siRNA-L was prepared through electrostatic interaction between folate doxorubicin liposo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 52 publications
2
51
0
Order By: Relevance
“…Combination therapy based on a siRNA and a chemical drug in a single NP platform has recently shown synergistic therapeutic efficacy in the treatment of many important diseases, such as cancer, skin inflammation, and rheumatoid arthritis 51-54. In this study, we developed an oral formulation (HA-functionalized NPs in hydrogel) for targeted co-delivery of a siRNA and a chemical drug to the key cells related to UC therapy (colonic epithelial cells and macrophages).…”
Section: Discussionmentioning
confidence: 99%
“…Combination therapy based on a siRNA and a chemical drug in a single NP platform has recently shown synergistic therapeutic efficacy in the treatment of many important diseases, such as cancer, skin inflammation, and rheumatoid arthritis 51-54. In this study, we developed an oral formulation (HA-functionalized NPs in hydrogel) for targeted co-delivery of a siRNA and a chemical drug to the key cells related to UC therapy (colonic epithelial cells and macrophages).…”
Section: Discussionmentioning
confidence: 99%
“…siRNA LPD Anti-EGFR Fab' The co-delivery LPD achieved the best control of tumor volume on orthotopic HCC-bearing mice, compared with the single agent-loaded LPD [59] Dox and BMI1 siRNA PEGylated cationic liposome Folic acid (FA) Bmi1 is an effective therapy target for siRNA-based cancer treatment, and it can be further improved by co-delivery of Dox via targeted liposomes [60] Docetaxel and VEGF siRNA Cationic liposome…”
Section: Cancer Resistance To Therapiesmentioning
confidence: 99%
“…The co-delivery formulation achieved the best control of tumor volume on orthotopic HCC-bearing mice, compared with the treatment of single agent-loaded LPDs. Yang et al encapsulated Dox in the aqueous core and adsorbed BMI1 siRNA on the surface of a folic acid (FA)-conjugated cationic liposome for the combination therapy of cancer [60]. The liposome prepared by thin-film hydration and membrane extrusion method consists of cholesterol (Chol), cationic lipid DOTAP, mPEG-DSPE and FA-PEG-Chol.…”
Section: Lipid-based Nanocarriers Liposomesmentioning
confidence: 99%
“…Empty liposomes (L), L-DOX-NPs, and L-miR-375/DOX-NPs were synthesized (Figure S1) as previously described 20 . The average particle sizes of L, L-DOX-NPs, and L-miR-375/DOX-NPs detected by dynamic light scattering (DLS) were 117.7 ± 0.5, 122.4 ± 0.3, and 162.5 ± 0.7 nm, respectively, which indicated that L-miR-375/DOX-NPs could accumulate in liver easily.…”
Section: Resultsmentioning
confidence: 99%